Harvesting and post-harvest handling of papayas in the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Papaya plants can be foud throughout the Caribbean region growing in backyards, scattered or inter-mixed with other fruit trees, in commercial, pure-stand plantings, or growing isolated in the wild.